Purification and characterization of a new β-lactamase OXA-205 from Pseudomonas aeruginosa. Issue 1 (December 2015) - Krasauskas, R.; Labeikytė, D.; Markuckas, A.; Povilonis, J.; Armalytė, J.; Plančiūnienė, R.; Kavaliauskas, P.; Sužiedėlienė, E.
Abstract Background We have identified a novel class 1 integron (1503 bp), namedIn671 in a clinicalPseudomonas aeruginosa isolate. Integron sequence analysis revealed two gene cassettes, one coding for a new OXA-type β-lactamase designated as OXA-205 and the other coding for theaadB gene that is responsible for aminoglycoside resistance. The 266 amino acid sequence of OXA-205 revealed that this β-lactamase belongs to the Ambler class D showing highest sequence homology to the OXA-2 sub-lineage. Our objective was to purify and characterize β-lactamase OXA-205. Methods Escherichia coli cells were transformed with a plasmid containing clonedbla OXA -205 gene fromP. aeruginosa . Purification of overproduced OXA-205 consisted of a single ion-exchange chromatography step. SDS-PAGE and isoelectric focusing were performed to determine the molecular mass and pI, respectively. Size-exclusion chromatography was undertaken to determine the OXA-205 oligomerization state. Substrate hydrolysis reactions were employed to assess enzyme kinetic parameters. Results Purification of OXA-205 yielded the enzyme with >95 % purity (as verified by SDS-PAGE). Approximate yield of the protein was estimated to be 20 mg per liter of culture. OXA-205 had a pI at 8.1, molecular mass of 26 kDa and a monomeric native structure. Kinetic analysis revealed that OXA-205 hydrolyzed narrow spectrum substrates, including ampicillin, carbenicillin, oxacillin, penicillin G, cefazolin and cefuroxime. Additionally, we observed a substrate inhibition profile towards carbenicillin and oxacillin, but not with ampicillin or penicillin G. Our results also show that OXA-205 conferred unusually high (among class D β-lactamases) resistance towards inhibition by NaCl. Conclusions OXA-205 can be considered a narrow spectrum monomeric β-lactamase that demonstrates unusually high resistance profile towards inhibition by NaCl.